REFORMASI BIROKRASI PENGURUSAN AKTA KELAHIRAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KAMPAR - Syilvia Nurhabibah Suarti; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
An agenda of reforms that carried out since 1998 addressed to all muslims andsocially, life including against the reformation the field of birokrasi.birokrasi as a publicinstitutions that therein there are human resources ( sdm ) are reliable, since the new orderdifficult touched change.Bureaucracy reform is important because we have to build the administrativesystem of its own and to find a way out to finish the big problems facing the governmentin providing services to the public. Bureaucracy reform is a business that mark the desireto change or Fix an organization a government that run errands the task of countries inthis matter public services to toward something better.Research is aimed to see bureaucracy reform in dept. of population and civilregistry based upon the factors affecting the implementation of reformation inbureaucracy in management birth certificate.The study is done at dept. of population andcivil registry district kampar.A method of research used in this research is a method of research descriptivewith data analysis and engineering data qualitative, through an interview observation andstudy kepustakaan.Who became an informer in this research is people district kampar,head of population and civil registry district kampar and employees in dept. of populationand civil registry district kampar.From the results of research that is done, found that bureaucracy reform in dept.of population and civil registry district kampar not run secaraefektif for the purpose ofreform has not been achieved, many factors inhibitors of the reformation in dept. ofpopulation and civil registry district kampar and the result of reform not yet obtained.Keywords : reforms, bureaucracy, birth certificate.